APPLICATION OF ACCOUNTING LEARNING USING STANDARDS OF PSAK CONSERVATION OF IFRS IN MEDIUM SCHOOL ACCOUNTING VOCATIONAL SCHOOL - Sakdiah, Khairani; Silalahi, Cita Ayni Putri (Journal of Community Research and Service, 2019)
The purpose of education at the opening of the 1945 Constitution in the fourth paragraph was clearly explained that, to educate the life of the nation and participate in carrying out world order. In accordance with the goals and ideals of the nation, various fields of science are needed by the State. To be able to progress and develop in accordance with the needs of the State, we must also follow the existing regulations that are binding in the agreement of states. Likewise, there is no escape in accounting learning that must be applied in schools, both in universities and high schools, which are mainly vocational high schools (SMK). As an example of accounting subjects, Accounting is a field of applied science that is used to see the financial existence of both the state, agencies, companies and organizations and others. International Financial Reporting Standards (IFRS) is the making of accounting reports that are adjusted to the standards of international financial reports, and almost all parts of the world in this world of accounting reporting use the IFSR standard. Because of that, almost all companies are required to use these standards in terms of financial statements making, educators are also obliged and participate in teaching these standards to students, both in universities and schools that have accounting majors can also apply this as teaching materials that are not left behind. The indicators used to measure the application of accounting learning by using standards are IFRS convergence PSAK, namely: Viewing and observing the behavior of actions taken by teachers in schools that are the object of research, whether using IFRS convergence accounting standards in teaching to provide material to students and adjustments between kurukulum given by dina education. The population in this study were the Accounting Department teachers who were in Langkat Regency. Data collection techniques in this study were using interviews, observation, documentation and questionnaires. The research method used in this study is descriptive analysis. And the results obtained as a whole in this study are the absence of teachers who apply accounting learning by applying accounting using IFRS standards because there is no directive from the education office to enforce these standards.Keywords: IFRS, BM-SMK, Accounting.